Precise macronutrient application can improve cane yield and nutrient uptake in widely spaced plant-ratoon cycles in the Indo-Gangetic plains of India - Kumar, Navnit; Rana, Lalita; Singh, A. K.; Pramanick, Biswajit; Gaber, Ahmed; Alsuhaibani, Amnah Mohammed; Skalicky, Milan; Hossain, Akbar (Frontiers in Sustainable Food Systems, 2023)
Introduction Sugarcane is a long-duration and nutrient-exhaustive crop. To improve nutrient use efficiency, the 4R nutrient stewardship approach comprises applying nutrients at the right time and place with the right method and at the right proportion. Improper nutrient management in such a nutrient-exhaustive crop will result in various nutrient losses and environmental pollution. Methods Concerning this, a field study was performed on calcareous soils of the lower Indo-Gangetic plains of India during two subsequent years at the Sugarcane Research Institute, RPCAU, India, to explore the effect of precise application of macronutrients (N and K) in different methods of applications. The application methods (broadcasting and band application) were maintained in the main plot, and split N and K applications were put in the subplots. Results and Discussion A highly significant difference was observed in the numbers of millable cane, cane, and sugar yield under the split applications of fertilizer. The decline in millable cane numbers, cane, and sugar yield due to the broadcasting method was to the tune of 17.5 and 17.6%, 14.8 and 17.1%, and 14.7 and 15.8% in plant and ratoon crops, respectively as compared to band placement of the fertilizers. Yield increased by 16.0 and 15.1% under plant and ratoon crops, respectively, with seven split applications of N and K compared to the control (two split of N and no split application of K). Band placement of N and K fertilizers markedly improved the nitrogen uptake (284.1 and 287.3 kg ha−1, in plant and ratoon, respectively) and phosphorus uptake (34.9 and 28.3 kg ha−1 in plant and ratoon, respectively) when compared to broadcasting. Application of N and K in seven splits resulted in better availability of nutrients in the soil, thereby facilitating the higher NPK uptake by the plants and ratoon both comparing two split applications of N and no splitting of K. From this study, it was observed that the band placement coupled with seven splitting of N and K is the best fertilizer application protocol, ensuring higher growth, yield, quality, and nutrient uptake of sugarcane in the calcareous soils of the Indo-Gangetic plains.